1985
DOI: 10.1128/iai.47.2.363-365.1985
|View full text |Cite
|
Sign up to set email alerts
|

Candidacidal activity of myeloperoxidase: therapeutic influence of the enzyme in vivo

Abstract: Mice were injected intravenously with Candida albicans blastospores to establish chronic renal infection. Seventy-five percent of the animals inoculated with 10(6) blastospores died as a consequence of infection during the subsequent 60 days of observation. Intraperitoneal administration of 10 mU of partially purified human myeloperoxidase 1 day after injection of the pathogen increased survival of the mice from 25 to 80% over this time period. Administration of myeloperoxidase complexed with soluble C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Our results obtained with MPO-deficient mice are similar to those obtained with neutrophil-depleted mice (15). Furthermore, intraperitoneal administration of purified MPO has been reported to increase the resistance of mice to Candida infection (50), suggesting that peritoneal neutrophils without MPO are impaired in their ability to protect against invasion from the intraperitoneal route. Collectively, these results indicate that neutrophils with MPO play a critical role against systemic candidiasis, especially in the lungs and kidneys, while other defense systems, such as the phagocytic function of macrophages, appear to be more effective in the brain, spleen, and liver.…”
Section: Discussionsupporting
confidence: 86%
“…Our results obtained with MPO-deficient mice are similar to those obtained with neutrophil-depleted mice (15). Furthermore, intraperitoneal administration of purified MPO has been reported to increase the resistance of mice to Candida infection (50), suggesting that peritoneal neutrophils without MPO are impaired in their ability to protect against invasion from the intraperitoneal route. Collectively, these results indicate that neutrophils with MPO play a critical role against systemic candidiasis, especially in the lungs and kidneys, while other defense systems, such as the phagocytic function of macrophages, appear to be more effective in the brain, spleen, and liver.…”
Section: Discussionsupporting
confidence: 86%
“…The susceptibility of hyphal and yeast‐form cells towards hNGE was very similar, reflecting their similar susceptibility to NET‐mediated killing (4–6 mg ml −1 ). The antifungals present in the granule extract are likely to include lactoferrin (Lupetti et al ., 2000) and myeloperoxidase (Lehrer and Cline, 1969b; Wright and Nelson, 1985). In contrast, a S. flexneri culture was sterilized by 1 mg ml −1 hNGE.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil MPO, which functions to generate HOCl in the phagocytic vacuole, seems to be a key antifungal host defense [7–15,17]. Our previous studies have shown that acetoacetate inhibits the chlorinating cycle of MPO, accelerating enzyme inactivation [21–23], and that it also inhibits neutrophil phagocytosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The primary host defense against C. albicans infections has been well documented to depend upon the enzyme MPO [8–13], a component of neutrophils which functions to generate the microbicidal species, hypochlorous acid (HOCl) from H 2 O 2 and Cl − in the phagocytic vacuole [8,14,15]. Since Lehrer and Cline's initial report of simultaneous disseminated candidiasis and MPO deficiency [7], a number of other studies have confirmed their conclusion that MPO is the major determinant of candidacidal activity in the human neutrophil [4,10,13,14,16,17]. The fact that C. albicans is the predominant pathogen in MPO deficiency can perhaps be attributed to its extreme resistance to H 2 O 2 which permits it to survive the MPO‐independent oxidative reactions of the neutrophil while other pathogens do not.…”
Section: Introductionmentioning
confidence: 99%